Effectiveness of MGSO4 Administration Against Prevention of Eclampsia in Severe Pre-Eclampsia in RSIA Resti Mulya in 2022 - Ulviana, Ulviana; Novita, Novita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: To determine the Effectiveness of Mgso4 Administration against Eclampsia Prevention in severe pre-eclampsia in RSIA Resti Mulya in 2022. Methods:  This study used the Quasy Experimental quantitative method, with a retrospective approach. The relationship between the two variables in this study was tested using the dependent paired t-test data analysis technique. The population of this study was all mothers who were severely eclampsia and received MgSo4 therapy as many as 43 respondents, using a total sampling of which all populations were made respondents. Results:  Frequency distribution of characteristics of respondents aged 30.8 years with a gestational age of 37.6 weeks with an obese Body Mass Index (30-39.5) of 39.5%, having a history of peer disease of 81.4%, and the number of multipara childbirth as much as 69.8%. Differences in the prevention of eclampsia (blood pressure and urine protein) in severe pre-eclampsia before and after administration of MgSo4, namely Sistol values of 163.8 vs 121.4. Diastole pressure value of 105.5 vs 80.4. urine protein 1.52. There is the effectiveness of mgso4 administration against the Prevention of eclampsia in severe pre-eclampsia at RSIA Resti Mulya in 2022 with a p-value value: 0.000. Conclusion:  The results of this study are that the administration of MgSo4 effectively prevents eclampsia in severe pre-eclampsia at RSIA Resti Mulya in 2022. Thus, it is expected to refer to the importance of giving MgSo4 to mothers with pre-eclampsia.